Dynamics of optical properties of sequentially diluted lucigenin aqueous solutions according to luminescence data - Tytik, Dmitrii L.; Kuzmin, Viktor I.; Souvorova, Olga V.; Revina, Alexandra A. (Frontiers in Chemistry, 2024)
The article discusses optical properties (luminescence) of diluted (24 dilution factor) lucigenin (Lc) aqueous solutions. Six series of Lc aqueous solutions, 50 samples in each series, were studied. The series were diluted on different days within random schedule, following unified procedure: the first sample in all series was Lc (C Lc = 8.2 × 10 -7 mol/L) stock solution, while the rest of the samples were obtained by successive dilution with the ratio of 24. For the first three samples, Lc luminescence intensity decrease appropriately complied with the exponential function model (the dilution ratio: none for the stock solution, for the second and the third -24 and 24 x 24 = 24 2 , respectively). Starting from the 4th sample for statistical processing of luminescence data, the 7 largest values were selected from the built rank distribution of emission intensity values. This method helps eliminate the influence of "random large bounces" when calculating the correlation coefficient. Up to 50th studied sample a challenging linear gradual decrease of the intensity of recorder photometric values was noted (correlation coefficients for all series being close to -0.9). Similar analysis of six reference series of pure water "dilution" samples did not exhibit any correlation between the highest emission values in the studied wavelength range (specific for Lc bandwidth, 480-505 nm) and sample's dilution number. It can be assumed that photometric values, recorded in the series of Lc sequentially diluted aqueous solutions after substance (Lc) elimination (theoretically expected after 13th sample within used experimental setup) could be attributed to the gradual destruction of long-lived aqueous structures formed in the process of hydration of Lc molecules during its dissolution.